Financial and Operational Problems of Micro Enterprise in Baglung and Parbat Districts - Karki, Bir Bahadur (Dristikon: A Multidisciplinary Journal, 2020)
The paper aims to explore major problems face by the micro enterprises. The objective of the research is to identify problems of micro enterprise in Baglung and Parbat districts. This study is based on mixed research design (quantitative and qualitative research). Data and information are collected through primary sources. Primary data are collected through structured questionnaire, focus group discussion, observations and field visit. Purposive and convincing sampling methods are used for selecting enterprises and entrepreneur respectively. A few statistical tools such as percentage are used for data analysis. There is not found such types of research work i.e. the financial and operational problems of micro enterprises in a particular area or district. After field visiting of micro enterprises in Parbat and Baglung district and focus group discussion with micro enterprises, it is found that micro enterprises have been facing various types of problems. Micro enterprises have been conducting with various problems such as production or input related problems and financial or economic related problems etc. Lack of working capital, higher interest rate on loan, not easily available raw materials in local market, problems regarding cold storage and warehouse, lack of adequate infrastructure like road, electricity, water, lack of other input materials for production, lack of skilled labour etc. are major problems faced by entrepreneurs as well as enterprises. Most of the micro enterprises are operating with a little fund, local resources and local skills. Government of Nepal should be managed special program to solve such types of problems of micro enterprises.